COGNITIVE MODELING BASED ON NONMANIPULABLE MECHANISMS OF THE MANAGEMENT DECISION MAKING - O. V. Lavrichenko (Системный анализ и прикладная информатика)
The article discusses some aspects of the balanced allocation of the limited resources of the Russian innovative companies. The author’s solution to this problem on the basis of non-manipulable mechanisms of decision-making. Author modified classical iterative algorithm of resource allocation when not transferable utility preferences of decision-makers, in relation to a multi-criteria problems parameterization balance for their distribution. In article defined and formalized terms of sufficiency and appropriateness for certain classes of these mechanisms usage for the development of the cognitive models of innovative management at limited resources.